Hubungan Kinerja Perawat Dengan Kepuasan Pasien Di Rumah Sakit X Kabupaten Semarang - Rismiyanto, Rismiyanto; Marchamah, Dwi Nur Siti; Arumsari, Wahyuni (Indonesian Journal of Health Community, 2024)
Nursing services have an influence on the quality of health services. A nurse has the responsibility to provide good performance when providing health services, where they are in direct contact with consumers. Nursing performance is based on established guidelines and standards which serve as a reference in health services. The aim of this research was to determine the relationship between nurse performance and patient satisfaction at Hospital X, Semarang Regency. The type of research used is quantitative with observational analytics. The research used a cross sectional approach. The population in this study were 1,653 inpatients in 2023 at Hospital X Semarang Regency. The sample for this study was 95 patients undergoing inpatient treatment at Hospital X Semarang Regency in 2023, calculated using the Slovin formula. The results of the study showed that the performance of nurses at Hospital Meanwhile, patient satisfaction at Hospital From this research, there is a relationship between nurse performance and patient satisfaction with a significant value (p-value) of 0.001 (<0.05).